Efficacy of New Fungicide and Biopolymer Based Against Root Rot of Safflower Caused by Trichoderma Macrophomina Phaseolina (Journal of Plant Disease Sciences, 2023)
Safflower (Carthamus tinctorius L.) has long been grown in India as a rainfed crop, and the country leads the world in both acreage and production. Diseases are major biotic restrictions in safflower production. Among the diseases, root rot caused by Macrophomina phaseolina is one of the most important safflower diseases, producing significant output losses. In the current work, four novel fungicides and two bioagents were tested in vitro against M. phaseolina. Thiophanate methyl 45% + Pyraclostrobin 5% FS (84.17%) inhibited the most mycelial development among the fungicides, followed by Tebuconazole 5.4% w/w FS (76.67%). However, in terms of bioagent, biopolymer-based Trichoderma harzianum (47.22%) inhibited mycelial growth the most, followed by Trichoderma harzianum Th4d WP (44.44%). In vivo evaluation of new fungicide molecules and bioagents revealed that, Thiophanate methyl 45% + Pyraclostrobin 5% FS was recorded 66.67 per cent wilt disease control followed by Tebuconazole 5.4% w/w FS 55.55% whereas biopolymer based Trichodermaharzianum showed 53.33 per cent wilt control followed by Trichoderma harzianum Th4d WPwith leastpercent disease control (11.12%).
Keywords: Fungicides; Macrophomina phaseolina; Root rot; Safflower